Design of Bridged Ring Modulators in Coaxial Magnetic Gears - Li Dehao; Xu Qing; Zhan Yang; Muhammad Salman Yousaf; Zhang Huidi (Jixie chuandong)
In the design of coaxial magnetic gears, the bridged modulating ring is proved to be an effective strategy for reducing the manufacturing difficulty and enhancing the mechanical strength of the structure. The design of modulating rings necessitates a comprehensive consideration of the factors including electromagnetic performances, mechanical strength, and manufacturing cost. This study investigates the design of bridged modulating rings employed in coaxial magnetic gears. By changing the design variables such as the thickness of the bridge, the proportion of modulation blocks, the number and diameter of clamping rods, a focused analysis is carried out to illustrate the variation pattern of the maximum torque of magnetic gears and the stress distribution in the bridged modulating rings with the change of these design variables, and a design method for bridged modulating ring is also proposed based on above analysis.